2010
DOI: 10.1158/1078-0432.ccr-09-2525
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles and Clinical Correlations of Degradome Components in the Tumor Microenvironment of Head and Neck Squamous Cell Carcinoma

Abstract: Purpose: Head and neck squamous cell carcinomas (HNSCC) are characterized by high morbidity and mortality, largely due to the high invasive and metastatic potential of these tumors, high recurrence rates, and low treatment responses. Proteinases have been implicated in several aspects of tumor growth and metastasis in a broad range of tumors including HNSCC.Experimental Design: Comprehensive expression profiling of proteinases [matrix metalloproteinases (MMPs), A disintegrin and metalloproteinase (ADAMs), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 46 publications
(71 reference statements)
6
100
1
2
Order By: Relevance
“…19 -21 SCC cells were cultured in Dulbecco's modified Eagle's medium supplemented with 6 mmol/L glutamine, nonessential amino acids, and 10% fetal calf serum. 20,21 HaCaT, a spontaneously immortalized, nontumorigenic human epidermal keratinocyte-derived cell line, 22 and the Ha-rastransformed tumorigenic HaCaT cell lines A5, II4, and RT3 23,24 (a gift from Dr. Norbert E. Fusenig, German Cancer Research Center, Heidelberg, Germany) were cultured in Dulbecco's modified Eagle's medium containing 10% fetal calf serum. G418 (200 g/mL) was added to the medium of the Ha-ras-transformed HaCaT cell lines.…”
Section: Cell Culturesmentioning
confidence: 99%
See 3 more Smart Citations
“…19 -21 SCC cells were cultured in Dulbecco's modified Eagle's medium supplemented with 6 mmol/L glutamine, nonessential amino acids, and 10% fetal calf serum. 20,21 HaCaT, a spontaneously immortalized, nontumorigenic human epidermal keratinocyte-derived cell line, 22 and the Ha-rastransformed tumorigenic HaCaT cell lines A5, II4, and RT3 23,24 (a gift from Dr. Norbert E. Fusenig, German Cancer Research Center, Heidelberg, Germany) were cultured in Dulbecco's modified Eagle's medium containing 10% fetal calf serum. G418 (200 g/mL) was added to the medium of the Ha-ras-transformed HaCaT cell lines.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Keratinocytes were cultured in keratinocyte basal medium 2, supplemented with SingleQuots (Cambrex Bioscience, Walkersville, MD), as previously described. 20,21 …”
Section: Cell Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 Upregulation of MMP1 appears to a conserved in squamous cell carcinomas from different anatomic locations including the head and neck and oral cavity. [67][68][69][70] Matrix metallopeptidases appear integral to tumorigenesis and have been targeted by inhibitors; however, clinical trials of advanced lung, prostate, pancreas, brain, and GI tract malignancies have shown little efficacy to date. 64,71 More data may be needed before a successful clinical trial is completed.…”
Section: P53 Signalingmentioning
confidence: 99%